2018
DOI: 10.1123/jmld.2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Perceived and Actual Motor Competence in Portuguese Children

Abstract: The aim of this study was to examine the relationship between actual (AMC) and perceived (PMC) motor competence in Portuguese children. A total of 200 children (111 [0.55%] girls) aged 5–9 years old participated in the study. The Pictorial Scale of Perceived Movement Skill Competence (PMSC) and the Test of Gross Motor Development-2 (TGMD2) were used to assess PMC and AMC, respectively. Mann-Whiney U was used to test the differences between sexes and age groups. The association between TGMD2 and PMSC scores was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…The capacity to recognize their MC in the late childhood has been confirmed in the analyzed global model of four factors (actual and perceived MC in object control and self-movement), which yields a moderate correlation between actual and perceived MC, both for object control and self-movement. Our results support the findings of Duncan and colleagues [18], Jaakkola and colleagues [63], and Lopes and colleagues [64] who also used specific measurements in the field of MC and where the perception of MC remains aligned with the actual MC.…”
Section: Discussionsupporting
confidence: 91%
“…The capacity to recognize their MC in the late childhood has been confirmed in the analyzed global model of four factors (actual and perceived MC in object control and self-movement), which yields a moderate correlation between actual and perceived MC, both for object control and self-movement. Our results support the findings of Duncan and colleagues [18], Jaakkola and colleagues [63], and Lopes and colleagues [64] who also used specific measurements in the field of MC and where the perception of MC remains aligned with the actual MC.…”
Section: Discussionsupporting
confidence: 91%
“…However, this does not mean the role of perceived MC in early years children should be disregarded. Barnett et al [17] found that perceived MC mediated the longitudinal associations between middle childhood PA and adolescent MC; additionally, actual and perceived MC are associated [2,4,12,19,42]. Therefore, inflated perceived MC may be an important component to encourage younger children’s MC engagement to influence future PA participation.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased perceived MC is associated with increased PA [16,17,18] and children’s perceived MC should be considered when attempting to increase PA [18]. Perceived MC has correlations with PA [7,11] and with actual MC [2,4,14,19]. However, there is a paucity of studies investigating how self-perceptions of MC, collectively and as LC and OC, mediates associations between PA and MC, suggested by Stodden and colleagues [5].…”
Section: Introductionmentioning
confidence: 99%
“…Outro aspecto observado nas pesquisas é a percepção mais elevada dos meninos especialmente em relação a dimensões da atlética da autoperceção de competência. Vários estudos nacionais 11,17,20,[29][30][31][32][33][34] e internacionais 26,[35][36][37][38] confirmam essa tendência. As crenças e valores culturais, especialmente em relação à atribuição de papéis sociais também têm influência sobre a construção da competência percebida.…”
Section: Auto-percepção De Competência Em Diferentes Faixas Etárias E Entre Meninos E Meninas: As Contribuicões Das Pesquisas Atuais Paraunclassified